Study on electrical resistivity model of soil-rock mixture - Chen, Songlin; Zhao, Mingjie; Wang, Kui (Frontiers in Earth Science, 2025)
Based on the established theory of electrical resistivity, models for the electrical resistivity of soil-rock mixture (S-RM) are developed from the perspectives of two distinct conductive media. Shear tests were conducted on the S-RM using a modified triaxial device, and electrical resistivity and deformation were measured simultaneously. The theoretical models were evaluated against the experimental results to assess its accuracy. The results indicate that as shear deformation increases, the deviatoric stress and electrical resistivity of S-RM sample exhibit an inverse relationship. The stress-strain-resistivity curve for S-RM differs from that of soil and concrete. When the confining pressure is low, the Maxwell conduction model effectively characterizes the resistivity changes of S-RM. However, as the confining pressure increases, its ability to characterize these changes diminishes. The relative error between the theoretical resistivity values derived from Maxwell conduction model and the measured values exhibits a discrete distribution, ranging from 1% to 14%. Notably, the maximum relative error reaches 13.61%. The series-parallel model demonstrates stable and exceptional resistivity characterization capability across varying rock contents and confining pressures. The distribution of relative errors is more concentrated, exhibiting a variation range of 3%–8%, and the maximum relative error is merely 7.16%. The available resistivity models combined with practical applications do indeed provide the possibility for the precise application of the electrical resistivity method in geotechnical engineering.